2021
DOI: 10.18632/oncotarget.27908
|View full text |Cite
|
Sign up to set email alerts
|

A high-content AlphaScreen™ identifies E6-specific small molecule inhibitors as potential therapeutics for HPV+ head and neck squamous cell carcinomas

Abstract: The incidence of human papillomavirus-positive head and neck squamous cell carcinoma (HPV + -HNSCC) has increased dramatically over the past decades due to an increase in infection of the oral mucosa by HPV. The etiology of HPV + -HNSCC is linked to expression of the HPV oncoprotein, E6, which influences tumor formation, growth and survival. E6 effects this oncogenic phenotype in part through inhibitory protein-protein interactions (PPIs) and accelerated degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The assay for establishing optimal ACE2 and S1 RBD binding was developed by initially cross-titrating the two labeled protein substrates, ACE2 tagged with biotin and S1 RBD tagged with 6xHis based on a protocol adapted from our previously published work [ 26 , 27 ]. Briefly, 5 μ L of each labeled protein was added to wells of a 384-well plate containing 5 μ L of blocking buffer solution.…”
Section: Methodsmentioning
confidence: 99%
“…The assay for establishing optimal ACE2 and S1 RBD binding was developed by initially cross-titrating the two labeled protein substrates, ACE2 tagged with biotin and S1 RBD tagged with 6xHis based on a protocol adapted from our previously published work [ 26 , 27 ]. Briefly, 5 μ L of each labeled protein was added to wells of a 384-well plate containing 5 μ L of blocking buffer solution.…”
Section: Methodsmentioning
confidence: 99%
“…We previously identified an E6 specific inhibitor, GA-OH, from a high content screen and have shown that it increases caspase 8 and p53 levels in HPV + cells (25). Given that expression of wildtype p53 has been identified as a critical biomarker for radiosensitivity in HNSCC and the role caspase 8 plays in apoptosis, we first investigated how GA-OH modulates radiosensitivity of 2 HPVand 3 HPV + cell lines.…”
Section: Effect Of Ga-oh On Radio-cytotoxicity As Compared To Cisplat...mentioning
confidence: 99%
“…We previously discovered an E6 inhibitor, GA-OH, and demonstrated that it can rescue pro-apoptotic molecules, including p53, and promote apoptosis (25). We therefore tested the efficacy of GA-OH in combination with radiation to evaluate radio-potentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these inhibitors, we recently discovered another inhibitor with a nonflavonoid scaffold (30 hydroxygambogic acid, or GA-OH) as a potential therapeutic for HPV + cancer cells. We demonstrated that GA-OH significantly inhibited the survival and growth of HPV + cell lines and displayed higher potency than did flavonols such as myricetin [ 73 ]. In the future, we hope to study whether this inhibitor will potentiate the activity of standard therapies in HPV-associated cells and how it interacts with E6.…”
Section: Therapeutic Targeting Of E6 Ppismentioning
confidence: 99%